Insulinoma: A Rare Cause of Hypoglycemia: Insulinoma: Uma Causa Rara de Hipoglicemia - Matta-Coelho, Cláudia; Monteiro, Ana Margarida; Marques, Olinda (Gazeta Médica, 2018)
Insulinoma is the most frequent pancreatic functional neuroendocrine tumour. The clinical presentation is variable and maymimic other diseases. A 61-year-old female patient, with several episodes of behavioural changes in the last 2 years. In one of these episodes, hypoglycemia was noted. The etiological study revealed inappropriately elevated values of insulin and C-peptide, consistent with endogenous hyperinsulinism. In spite of normal abdominal computed tomography, magnetic resonance and somatostatin receptors scintigraphy, the endoscopic ultrasound showed an infracentimetric pancreatic lesion compatible with insulinoma. The patient was submitted to surgical excision of the lesion, and remains asymptomatic and free of disease. We emphasize the unspecific clinical presentation and the small dimension of the lesion, which may lead to a significant time gap between the start of the symptoms and the treatment. Received: 02/06/2017 - Accepted: 27/10/2017